Evaluation on the effect of the support parameters and slice thickness on the prototype quality in fused deposition modeling - 186803 Ahmad Faizal Salleh; Safian Sharif, supervisor; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Mekanikal (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Mekanikal -Teknologi Pembuatan Termaju)) - Universiti Teknologi Malaysia, 2006